Predicting Factors of Deliberated Self-Harm among Thai Adolescents - Singtakaew, Arunothai; Chaimongkol, Nujjaree; Hengudomsub, Pornpat (Journal of The Royal Thai Army Nurses, 2021)
This descriptive predictive research aimed to examine deliberate self-harm (DSH) and determine its predictors. A multi-stage random sampling was used to recruit the sample of 360 Thai adolescents aged 10-19 years who were studying in secondary schools in northern Thailand. The data were collected from July 2019 to January 2020. The research instruments were 7 self-report questionnaires. Their consistency reliability ranged from 0.81-0.89. Descriptive statistics, Pearson’s correlation coefficients, and stepwise multiple regression were used for data analyses. Results revealed that the participants had their DSH in the past six months about 3-14 times with a mean score of 6.11 (SD = 2.83). The best predicting factor was stress (ß = .271, p <.001), following by sex (male) (ß = .197, p <.001), student-school connectedness (ß = .193, p <.001), self-control (ß = -.187, p <.001), and resilience (ß = -.172, p <.01). These five significant predicting factors were together accounted for 18.80% (R2 = 0.188, Adj. R2 = 0.177, F5,354 = 16.422, p <.001) in the variance of DSH. These findings suggest that school nurses, teacher or related interdisciplinary personnel could be utilize as foundation knowledge to develop activities or programs to strengthen student-school connectedness, self-control and resilience, as well as diminish stress among Thai school adolescents to prevent DSH in male and female adolescents by more focused on male adolescents.